Students’ Perception of Using Note-taking in Listening - Anggun Siswahyuni; Melvina Melvina; Sesmiyanti Sesmiyanti (English Teaching and Linguistics Journal (ETLiJ), 2023)
Note taking is an vital academic skill. Van de Meer, (2012) points out that “Note - taking in lectures is often taken to be the distinguishing characteristic of learning at university”. Note-taking brings high effectiveness on comprehension. Kiewra, (1991) indicates that taking notes during lessons helps students understand what is taught easier and then they can reach the objectives of the course more comfortable. The majority of students have difficulties to follow listening activity. They felt under pressure to understand every word. It means that the students have difficulty in catching the information from the speaker S. Sumihatul,(2012) states many factors that the student feels difficult when studying listening in English, for example: material too fast to be heard to forget what they have heard listen, don't know the meaning of the spoken English word or heard because of the limited English vocabulary they have, not concentrating on the material being heard, not understanding orders explain verbally, lazy in learning or no motivation to learn, and many more factors. As a result, the students have hearing problem and most of them have low motivation to learn listening Moreover, note-taking is also very helpful for students as a strategic way to catch the points of what they listen. The note becomes a material which they use to recall what teachers and professors have explain to them. Milligan (2014) explains note-taking as an effective way in the learning process because through note-taking students can incorporate a lot of sense. For example, students need sharp thinking and listening skills to determine important information to note. It is known that students need something to help improve their listening skills. Therefore, this study tries to find out the students' perceptions of the use of note taking on their listening skills. It is hoped that by knowing the results of this study, it can be referred to and the information investigated in depth in the future to find some possible strategies that can be recommended to students to improve their listening.